STRUKTUR PENYAJIAN TARI RADDAT KOKO DI DESA SEKUDUK KECAMATAN SEJANGKUNG KABUPATEN SAMBAS - Khairul Anami; Imma Fretisari; Winda Istiandini (Universitas Tanjungpura, 2020)
AbstractThe study aimed to describe the structure of the Raddat Koko dance performance in Sekuduk Village, Sejangkung District, Sambas Regency. The research problems included motion, clothing, makeup, musical accompaniment, upper design, floor design, dramatic design, and the Raddat Koko dance performance. This research was conducted through descriptive methods, in the form of qualitative research and choreographic approaches. The sources of research data were observations, interviews, and documentation of interviewees namely Bahri, Kusnadi and Jurita. The techniques of data validity used triangulation and the techniques of data analysis were systematically collected and analyzed. The research findings showed that there were15 varieties of Raddat Koko dance divided into the initial, the middle (content) and the final movements. The costume employed in Teluk Belanga gown, belts, headbands, veils, and realist makeup. The upper design was high, low, medium, angular, symmetrical and asymmetrical. The dramatic design was in the form of multiple cones, with horizontal and zig-zag floor design. Groups design was in unison and turn. Music accompaniment used tar, long drums, and an Islamic rhyme. Stage located at Proscenium, arena, and field (home yard).Keywords: Performances Structure, Raddat Koko Dance, Sekuduk Village.